Political science: a primer - Islam, Syed Serajul; Moten, Abdul Rashid (Thomson Learning, 2005)
This book is intended to introduce students to the study of politics, and make them aware of their civil rights and responsibilities as responsible citizens. This primer focuses on issues in the hope that the excitement of politics will interest students to learn more about politics. It also examines the nature and purpose of government, in particular the Malaysia government, the responsibility of a citizen, the nature of law, and the prospects of development through elections, political parties and leadership. One of the chapters discusses some of the well-known thinkers which political science beginners would find familiar. This primer shows the relevance of politics to Islam as a way of life. It also examines 14 issues of importance and concludes with a chapter on the various dimensions of the government and politics in Malaysia.